Implementation of the Project-Based Experiential Learning Model in Religious Education at Elementary Schools - Zakiyah BZ; Wiwis Rohmatul Ummah; Zulfa Umi Zakiyah; Lailatul Muarifah; Samira Agoro (Journal of Islamic Education Research, 2024)
This article explores the application of the project-based experiential learning cycle (ELC) model in religious education subjects at MI Nurul Mun'im, Karanganyar, Paiton, Probolinggo, Indonesia. The ELC model, emphasizing experiential processes, facilitates education and fosters a deeper understanding of Islamic religious studies. The implementation involves six stages: the preliminary (opening stage), experiencing (experience), reflection, discussion, exploration, and concluding (closing stage). This study employs a qualitative descriptive approach with action research as the research type, where the researcher serves as both a key instrument and an active participant. Data collection methods include interviews, documentation, and observations. The research was conducted at Madrasah Ibtidaiyah Nurul Mun'im, Paiton, Probolinggo, using a random sampling technique to select students from grades V and VI. The study also highlights the dynamic and innovative development processes, curriculum advancements, and the transformation of scientific approaches at Elementary Schools.